Linkage Between Tourism And Agricultural Micro and Small Enterprises In Kediri (East Java – Indonesia) - Putra, Yudiarto Perdana; Sudarmiatin; Wardana, Ludi Whisnu Wardana (Universitas Kadiri, 2023)
Each region has potential resources that can be utilized. Agricultural tourism development is an alternative that can encourage economic potential, such as developing small and medium enterprises. This research aims to analyze the development of agro-based tourism in Kediri, East Java. The type of research is qualitative, with data collection carried out by interviews, documentation, and observation. Based on the research that has been carried out, it can be concluded that the development of agro-tourism in Kediri includes Community-Based Tourism. In developing agrotourism, there are several factors, such as age, gender, education, employment, and length of stay, but education cannot be a supporting factor. For consideration, the Department of Agriculture and the Tourism Office in Kediri will provide training to process agricultural products for farmer groups and communities, complete facilities and infrastructure, and promotional aspects.